FEA of contact between scleral buckle and human eye tissues - Shukla, Vishal V.; Sawalakhe, Pranil V.; Shende, Pooja (Asia-Pacific Journal of Science and Technology, 2022)
Human eye is one of the physiologically complex organs of human body. With aging or may be because of family history, eye problems are prevalent. One such problem is Retinal Detachment. It is the disorder of eye in which retina separates from layer underneath. To solve this problem, Scleral Buckling surgery is the recommended solution. The surgery is established by depressing the eye with band or buckle parallel to the area of retinal breaks. As a result, spherical shape of human eye changes to egg like structure. Changes in shape of eye may pose treatment challenges in repair of eye tissues. This research work aims to verify physical effectiveness and surgical after effects of scleral buckle surgery. In this research, response of a human eye deployed with scleral buckle is investigated by Finite Element Method (FEM). The study throws light upon problems raised after ring is indented on the eye. Human Eye model has been created by referring dimensions from literature & solution is obtained by applying suitable boundary conditions and loads. The highest displacement of 3.3596 mm for pressure value 0.7 MPa is found in Vitreous Humor. A maximum stress of 4050.3 KPa for 0.7 MPa pressure value is found at contact surface of sclera where ring touches Scleral outer surface. The maximum displacement of 3.3481 mm & a stress of 35.9 KPa at 0.7 MPa pressure is observed on retina typically in the regions of likely detachment. This indicates scleral buckle could facilitate restoration of detachment.